Comparative life cycle assessment of bio‐based insulation materials: Environmental and economic performances. Issue 6 (2nd April 2021) - Schulte, Maximilian; Lewandowski, Iris; Pude, Ralf; Wagner, Moritz
Abstract: Insulation materials decrease the final energy consumption of buildings. In Germany, fossil and mineral insulations dominate the market despite numerous life cycle assessments (LCAs) showing that bio‐based insulations can offer environmental benefits. Evaluating the results of such LCAs is, however, complex due to a lack of comparability or costs considered. The objective of this study is comparing bio‐based insulations under equal conditions to identify the most environmentally friendly and cost‐efficient material. For this purpose, a comparative LCA and life cycle costing (LCC) were conducted from "cradle to grave" for four bio‐based and two nonrenewable insulations. The bio‐based insulation materials evaluated were wood fiber, hemp fiber, flax, and miscanthus. The nonrenewable insulations were expanded polystyrene (EPS) and stone wool. Key data for the LCA of the bio‐based insulations were obtained from preceding thermal conductivity measurements under ceteris paribus conditions. Eighteen environmental impact categories were assessed, and direct costs were cumulated along the life cycle. Results show that the most environmentally friendly bio‐based insulation materials were wood fiber and miscanthus. A hotspot analysis found that, for agriculturally sourced insulations, cultivation had the largest environmental impact, and for wood fiber insulation, it was manufacturing. The use phase (including installation) constituted a cost hotspot. The environmental impacts of end‐of‐life incineration were strongly influenced by the fossil components of the materials. Overall, bio‐based insulations were more environmentally friendly than EPS and stone wool in 11 impact categories. The LCC found EPS and miscanthus insulation to be most cost‐efficient, yet market integration of the latter is still limited. It can be concluded that miscanthus biomass is an environmentally and economically promising bio‐based insulation material. Comparability of the environmental performance of the bio‐based insulations was increased by applying the same system boundary and functional unit, the same impact assessment methodology, and the preceding ceteris paribus thermal conductivity measurements. Abstract : Insulation materials decrease the final energy consumption of buildings. In Germany, fossil and mineral insulations dominate the market despite numerous life cycle assessments (LCAs) showing that bio‐based insulations can offer environmental benefits. Evaluating the results of such LCAs is, however, complex due to a lack of comparability or costs considered. The objective of this study is comparing bio‐based insulations under equal conditions to identify the most environmentally friendly and cost‐efficient material. Results show that the most environmentally friendly bio‐based insulation materials were wood fiber and miscanthus. In addition, miscanthus insulation is most cost‐efficient, yet market integration is still limited.